Polymorphisms in Gap Junction Proteins and their Role in Predisposition of Acute Myocardial Infarction in Egyptians - El Tahry, Fadwa A.; Hashad, Ingy M.; Abdel Rahman, Mohamed F.; Gad, Mohamed Z. (Current Pharmaceutical Biotechnology, 2017)
Background: Connexin (Cx) proteins are the building blocks of gap junctions. Among these, Cx37 and Cx40 are expressed on vascular system and reported to have cardioprotective role. Linking polymorphisms in genes coding for Cx and coronary artery disease (CAD) risk showed conflicting results in different populations. None has been studied before in Egyptians. Therefore, the aims of this study were to investigate the influence of Cx37 C1019T and Cx40 A71G polymorphisms on the predisposition of acute myocardial infarction (AMI) in Egyptians, to study linkage disequilibrium (LD) and combined effects of single nucleotide polymorphisms (SNPs) and to correlate the genotypes with sVCAM-1 serum levels. Methods: Total of 201 Egyptian subjects were recruited for the study. They were divided into 104 AMI patients and 97 healthy controls. Genotypes for each participant were determined using a polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP). Serum sVCAM-1was measured by ELISA. Results: Allele frequencies for both Cx37 and Cx40 were not significantly different between AMI and Controls (p=0.93 and p=0.26 respectively). Moreover, studying the dominant and recessive models concluded that none of the genotypes was a risk factor. Both SNPs were not in LD (R2=0.0027). Serum analysis showed higher levels of sVCAM-1 in AMI patients (p<0.0001). sVCAM-1 levels were not significantly different among SNPs (Cx37; p=0.244 and Cx40; p=0.266). Conclusion: This study shows that Cx37 C1019T and Cx40 A71G polymorphisms are not associated with cardioprotective role in Egyptians. Moreover, both SNPs are inherited separately and none of the genotypes were associated with higher sVCAM-1 levels.
Keywords: C1019T polymorphism